(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Kotelnikova I.V. Keywords: free Indirect Style, author, character, reader, point of view. The article studies the peculiarities of the author’s representation of the character’s thoughts in the aspect of a variety of perspectives, including his own. Free Indirect Style proves to be relevant for the reader in the sense that it creates the mutuality with the character which is mediated by the presence of the author. This kind of style gives the author a possibility to show his own attitudes towards the character whose thoughts are being represented. Its communicative structure is accumulated on its formal and syntactic structure, i.e. is external, actualizing the speakers’ images which interact with the reader who perceives the text.